CONCEPT AND APPLICATION OF EDUCATION MANAGEMENT FUNCTIONS - Rahman, Yudi Ardian (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2022)
Education in Indonesia embraces the concept of lifelong education. Therefore, education is the responsibility of the government, family and community. In order for the goals of national education to be realized, education itself requires good management. Management of education both by the government and the private sector for school and out-of-school education pathways at every type and level of education is needed in order to achieve national education goals. Education units established by the government are organized by the Minister of Education and Culture or other ministers, while education units established by the community are organized by foundations or social bodies. Principals at the primary and secondary education levels, rectors at the university / institute level, chairpersons at the academy / school level are responsible for organizing educational activities, school administration, fostering other education personnel and utilizing and maintaining facilities and infrastructure. Keywords: Concept, Implementation of Management Functions, Education